Effective Leadership in Iranian Higher Education - Hamidifar, Fatemeh (SFIMAR Research Review, 2012)
This article is based on the literature reviews aimed to analyze the factors affecting the leadership effectiveness of administrators in Iranian higher education. This is to study the academic leadership and to explore the requirement factors of effective academic leadership in Iranian universities. On the base of the theories and previous studies it could be concluded that effective academic leaders in Iran are in line with: set direction and goals, have clear vision, be efficient manager, recognize the new opportunities, have efficient human resource management by motivating and inspiring them to perform effectively and develop them, be attentive listener to learn how to improve their leadership qualities, constant improving teaching and research leadership, and create culture of trust and respect through effective communication. In order to perform effectively they also need to have certain characteristics such as creative problem solving, situation analysis, coaching, honesty, fairness, integrity, trustworthiness and competence. Furthermore, this paper is discussed the challenges and barriers which academic leaders in the managerial positions are confronting. Many barriers and challenges to academic leadership could be incorporated in financial resource, conflicting between faculty members, inappropriate selection conditions in management, inconsistency of academic leadership, lack of stability in educational management and ethical perspectives, inability to change the Institution culture, lack of CPD, centralization, inappropriate organizational structure, technology, social and political phenomenon.